A new species of the fish genus Arctozenus from the Kerguelen Islands, with comments on the lost teeth in adults (Aulopiformes: Paralepididae) - Ho, Hsuan-Ching; Duhamel, Guy (Zootaxa, 2019)
A new cryptic species of spotted barracudina, Arctozenus australis sp. nov., is described from the Kerguelen Islands, in the Indian Ocean sector of the Southern Ocean. It differs from the only congener, Arctozenus risso (Bonaparte, 1840), in the reduction of pigments on body, a more slender body, and longer head, snout and jaws. A neotype is designated for Paralepis risso Bonaparte, 1840 and Paralepis borealis Krøyer in Gaimard (1847). Note on synonymy of Paralepis risso is provided. Observation of adults of Notolepis annulata, Magnosudis prionosa and Paralepis coregonoides found loss of teeth on jaws and gill arches, suggesting more species in the subfamily Paralepidinae may commonly possess this character in adults.